Transformation of Reading Literacy In Elementary School Students During The Covid-19 Pandemic: A Literature Review - Hilma Mustika Fauziyyah; Prana Dwija Iswara (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
The COVID-19 pandemic has changed learning patterns and significantly impacted elementary school students’ reading literacy. This study aims to analyze changes in elementary school students’ reading literacy practices during the pandemic through a systematic review of recent research. The Systematic Literature Review (SLR) method was applied by referring to the PRISMA guidelines. The inclusion criteria for articles were 1) in the form of journal articles, 2) published in the 2020-2024 period, 3) indexed by scopus, 4) using English, 5) complete article sections, and 6) relevant to reading literacy at the elementary school level. A total of 519 articles from the Scopus and PubMed databases were selected to obtain 22 articles that met the criteria. Based on the analysis of research articles, it was found that the COVID-19 pandemic caused a decline in students’ reading literacy. This is due to several key factors. The first factor is the school closure policy. The second factor is the readiness of online learning. The third factor is the socio-economic background of students. The fourth factor is technology accessibility. These four factors contribute to gaps in accessibility of technology and the quality of learning received by each student. In addition, the educational adaptation to strengthen reading literacy during the pandemic includes holding reading teaching enrichment programs, using technology to support learning, and implementing appropriate reading teaching methods.